A redox-mediator pathway for enhanced multi-colour electrochemiluminescence in aqueous solution. Issue 2 (15th December 2021) - Kerr, Emily; Hayne, David J.; Soulsby, Lachlan C.; Bawden, Joseph C.; Blom, Steven J.; Doeven, Egan H.; Henderson, Luke C.; Hogan, Conor F.; Francis, Paul S.
Abstract : A water-soluble Ir(iii ) complex is shown to enhance the 'remote' mechanism of the most widely used co-reactant ECL reaction of tris(2, 2′-bipyridine)ruthenium(ii ) with tripropylamine. Abstract : The classic and most widely used co-reactant electrochemiluminescence (ECL) reaction of tris(2, 2′-bipyridine)ruthenium(ii ) ([Ru(bpy)3 ] 2+ ) and tri- n -propylamine is enhanced by an order of magnitude by fac -[Ir(sppy)3 ] 3− (where sppy = 5′-sulfo-2-phenylpyridinato- C 2, N ), through a novel 'redox mediator' pathway. Moreover, the concomitant green emission of [Ir(sppy)3 ] 3− * enables internal standardisation of the co-reactant ECL of [Ru(bpy)3 ] 2+ . This can be applied using a digital camera as the photodetector by exploiting the ratio of R and B values of the RGB colour data, providing superior sensitivity and precision for the development of low-cost, portable ECL-based analytical devices.